2021
DOI: 10.18632/aging.202911
|View full text |Cite
|
Sign up to set email alerts
|

Circ_0007841 accelerates ovarian cancer development through facilitating MEX3C expression by restraining miR-151-3p activity

Abstract: The critical importance of circular RNAs (circRNAs) in human cancers, including ovarian cancer, has been discovered in the recent years. However, the roles of circ_0007841 in ovarian cancer remain unknown. In the current study, it was found that circ_0007841 expression was upregulated in ovarian cancer tissues and cell lines. Upregulation of circ_0007841 in patients with ovarian cancer predicts poor prognosis. Loss-of-function experiments discovered that circ_0007841 knockdown suppressed the proliferation, mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…For instance, circ_0026123 silencing could inhibit the proliferative and migratory capacities of ovarian cancer cells by miR-124-3p/Enhancer of zeste homolog 2 (EZH2) axis, thereby inhibiting tumor malignant process [ 9 ]. An up-regulated circ_0007841 was discovered in ovarian cancer, and circ_0007841 enhanced cancer cell metastasis and growth in vitro and in nude mice by up-regulating Mex-3 RNA Binding Family Member C expression through competitively adsorbing miR-151-3p, indicating an oncogenic role of circ_0007841 in ovarian cancer [ 10 ]. Besides, upregulation of circ_0007874 inhibited the migration and proliferation of ovarian cancer cells by competitively adsorbing miR-760 and up-regulating suppressor of cytokine signaling 3 (SOCS3) expression [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, circ_0026123 silencing could inhibit the proliferative and migratory capacities of ovarian cancer cells by miR-124-3p/Enhancer of zeste homolog 2 (EZH2) axis, thereby inhibiting tumor malignant process [ 9 ]. An up-regulated circ_0007841 was discovered in ovarian cancer, and circ_0007841 enhanced cancer cell metastasis and growth in vitro and in nude mice by up-regulating Mex-3 RNA Binding Family Member C expression through competitively adsorbing miR-151-3p, indicating an oncogenic role of circ_0007841 in ovarian cancer [ 10 ]. Besides, upregulation of circ_0007874 inhibited the migration and proliferation of ovarian cancer cells by competitively adsorbing miR-760 and up-regulating suppressor of cytokine signaling 3 (SOCS3) expression [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs are a kind of short (~ 22 nt) non‐coding RNA, which are also shown to play vital roles in DN progression 26 . MiR‐151‐3p is a functional miRNA, which has been shown to exert anticancer effects on many types of cancers, such as colon cancer, breast cancer, ovarian cancer and so on 27 , 28 , 29 . In DN, An et al .…”
Section: Discussionmentioning
confidence: 99%
“…MiR-NAs are a kind of short (~22 nt) non-coding RNA, which are also shown to play vital roles in DN progression 26 . MiR-151-3p is a functional miRNA, which has been shown to exert anticancer effects on many types of cancers, such as colon cancer, breast cancer, ovarian cancer and so on [27][28][29] . In DN, An et al 12 showed that miR-151-3p acted as a target of hsa_circ_0003928 to participate in hsa_circ_0003928-induced ROS overproduction and inflammatory response in human renal epithelial cells HK-2 under HG treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, circPLEKHM3 exerts oncogenic effect in OC cells by targeting the miR-9/BRCA1/DNAJB6/KLF4/AKT1 axis, and affects EMT as well as taxol resistance ( Zhang L. et al, 2019 ). Circ_0007841, as a ceRNA for miR-151-3p promotes the expression of MEX3C, and recovery of MEX3C levels recovers the proliferation, migration, and invasive ability of OC cells ( Huang et al, 2021 ). CircWHSC1 mediates upregulation of downstream targets MUC1 and hTERT expression via sponge-mediated miR-145 and miR-1182 ( Zong et al, 2019 ).…”
Section: The Function Of Circrnas In Ovarian Cancermentioning
confidence: 99%